Implementasi Model Pembelajaran Kooperatif Tipe Team Game Tournament (TGT) Dalam Melatih Berfikir Kritis Peserta Didik - Qurrotulayunsufyan; Mohammad Sugi Hartono (Indonesian Journal of Islamic Educational Review, 2024)
Critical thinking skills in mathematics are very important to develop, for this reason it is necessary to have a mathematics learning process that involves students actively, especially in the learning process in the classroom. The aim of this research is to determine the level of students' critical thinking abilities in learning using the Teams Games Tournament (TGT) model, as well as to determine the factors that inhibit and support learning using the Teams Games Tournament (TGT) learning model. The type of research used is qualitative research. Data collection techniques use observation. Meanwhile, the data analysis technique used is descriptive interpretative. The results of the research show that the Teams Games Tournament (TGT) learning model really helps students understand the learning material. One of the things that supports learning using the Teams Games Tournament (TGT) model is the supporting media used, while the inhibiting factor in learning using the Teams Games Tournament (TGT) model is the lack of time in carrying out the learning process.